2018
DOI: 10.1007/s00330-018-5495-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging in the characterisation of rectal cancer: utilizing the most repeatable region-of-interest strategy for diffusion parameters on a 3T scanner

Abstract: • DKI using a 3T scanner is feasible for assessing rectal cancer. • ROI and slice protocol show considerable influence on DKI parameters. • DKI parameters exhibit excellent repeatability using whole-tumour slice-outline ROI on 3T scanner. • DKI has considerable diagnostic value for the estimation of rectal cancer characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The interobserver agreement was proved to be good to excellent for the whole‐tumor volume histogram metrics of DW‐MRI‐derived parameters (ADC, D, K), as reported in our previous study with the same observers . Furthermore, whole‐tumor slice (WTS)‐outline ROI resulted in the best intra‐ and interobserver ICC, compared with single and three slices ROI analysis . Therefore, whole‐tumor measurement performed by a single radiologist was regarded as sufficient and used for further analysis in this study.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…The interobserver agreement was proved to be good to excellent for the whole‐tumor volume histogram metrics of DW‐MRI‐derived parameters (ADC, D, K), as reported in our previous study with the same observers . Furthermore, whole‐tumor slice (WTS)‐outline ROI resulted in the best intra‐ and interobserver ICC, compared with single and three slices ROI analysis . Therefore, whole‐tumor measurement performed by a single radiologist was regarded as sufficient and used for further analysis in this study.…”
Section: Methodssupporting
confidence: 65%
“…25 Furthermore, whole-tumor slice (WTS)-outline ROI resulted in the best intra-and interobserver ICC, compared with single and three slices ROI analysis. 26 Therefore, whole-tumor measurement performed by a single radiologist was regarded as sufficient and used for further analysis in this study.…”
Section: Image Analysismentioning
confidence: 99%
“…We suggested that there might be selection bias placing small size-fixed round ROIs. A recent study [20] suggested that to analyze a larger number of pixels may result in more reproducible results for the measured parameters. Furthermore, We chose consecutive three slices of ROIs (the slice with the prominent lesion section and the adjacent up and down slices), thus could decrease the deviation of sampling between cases and increase the reliability of results [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen healthy persons aged 28-43 years old (average (35.9±4.2) were selected as the control group during the same period. All subjects signed informed consent (12). Based on this setting, the migration and movement of breast cancer cells (lesions) were studied.…”
Section: Research Methods Of Breast Cancer Cell Migration and Movement-based On Intravoxel Incoherent Motion Imaging Research Datamentioning
confidence: 99%